Pregnancy with pancytopenia: An Observational Study - H S Sridevi (Wolters Kluwer Medknow Publications, 2020)
Background: Pancytopenia is the reduction in all three major cellular elements of the blood; hence it is the simultaneous presence of anemia, leukopenia and thrombocytopenia. Pancytopenia is associated with many maternal and fetal complications during pregnancy like maternal sepsis, postpartum hemorrhage, pre-eclampsia and preterm labor, IUGR and intrauterine fetal demise. Methods: The study was conducted at BLDE (Deemed to be) University, Shri B. M. Patil Medical College Hospital, and Research Centre. It's an observational study done from November 2019-April 2020. The participants enrolled in the study were subjected to further clinical and laboratory evaluation and followed for a feto-maternal outcome. Results: The incidence of pancytopenia with pregnancy in this study was 3% and all the patients were vegetarian by diet along with vitamin B12 and folic acid deficiency. They were associated with different maternal and fetal complications. Conclusions: Proper dietary counseling and well-balanced dietary plans even with plant originate food can prevent micronutrients deficiency and avoid deleterious consequences like pancytopenia.